2011
DOI: 10.1161/circulationaha.111.030379
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of Abdominal Aortic Aneurysm Among 65-Year-Old Swedish Men Indicates a Change in the Epidemiology of the Disease

Abstract: Background-Screening elderly men with ultrasound is an established method to reduce mortality from ruptured abdominal aortic aneurysm (AAA; Evidence Level 1a). Such programs are being implemented and generally consist of a single scan at 65 years of age. We report the results from screening 65-year-old men for AAA in middle Sweden. Methods and Results-All 65-year-old men (nϭ26 256), identified through the National Population Registry, were invited to an ultrasound examination. An AAA was defined as a maximum i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
138
3
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 404 publications
(150 citation statements)
references
References 27 publications
7
138
3
2
Order By: Relevance
“…These programmes have now reported a much lower prevalence of 1.9% in England and 1.7% in Sweden, respectively. 11,12 As well as the decline in incidence of clinically relevant aneurysms in men in England, Wales and Scotland, the age at which these aneurysms present has increased by 5-10 years. 13 Reports from other countries also show that aneurysm-related mortality is no longer increasing.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…These programmes have now reported a much lower prevalence of 1.9% in England and 1.7% in Sweden, respectively. 11,12 As well as the decline in incidence of clinically relevant aneurysms in men in England, Wales and Scotland, the age at which these aneurysms present has increased by 5-10 years. 13 Reports from other countries also show that aneurysm-related mortality is no longer increasing.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…1 The overall prevalence is 2% in men above 65 years of age, 2 four times higher in men than women, 34 but with a worse prognosis in women than men. 56 While the annual incidence and prevalence rates of AAA continue to decline, 279 and mortality rates have dropped to just 2% in 2010, 10 death from all aortic aneurysms remains the 16th leading cause of death in the USA among those aged above 65 years. 10 The greatest mortality risk is among those previously undiagnosed who may present with ruptured AAA.…”
Section: Introductionmentioning
confidence: 99%
“…Studies reported an AAA prevalence in the range of 4–7% for men aged 65 years or more [8,9] and increasing rates in incidence [10] and mortality [11]. Recent studies have shown a decrease of AAA prevalence to less than 2% in men aged ≥65 years [12] and there is evidence that the incidence and mortality from AAA is also declining [13]. These results may reflect the positive effects of reduced exposure to risk factors.…”
mentioning
confidence: 99%